The Relationship Between Achievement Motivation And Learning Environment With Science Learning Outcomes Of SD Negeri 07 Pagi Rawamangun Students, Pulogadung District, East Jakarta - Cayati Cayati; Alfiani Damayanti; Irfan (Kappa Journal, 2024)
Research has been conducted on the effect of Multi Leaf Collimator (MLC) on the dose received by the head of brain cancer patients at Sanglah Hospital, Denpasar. This analysis aims to determine the effect of using MLC on dosing to brain cancer patients using Cobalt 60 (Co-60) teletheraphy. The dose given at TPS was 200 cGy but after using MLC the dose was received because MLC protects healthy organs around the irradiation field. If the dose given is still within the range of -5  % and +7  %, it is still acceptable. The amount of radiation dose that can be reduced by using MLC in this study was 1,35 % for brain cases and 0,12 % for Glioblastoma cases. The result of the hypothesis testing shows: (1) there is a relationship positive and significant between achievement motivation with science learning outcome, (2) there is a relationship positive and significant between learning environment with science learning outcome, and (3) there is a relationship positive and significant jointly between achievement motivation and learning environment with science learning outcome.